Editors and Guidelines of the SIPATAHOENAN Journal, Issue of October 2015 - SIPATAHOENAN, Editor Journal (ASPENSI, 2015)
SIPATAHOENAN journal will provide a peer-reviewed forum for the publication of thought-leadership articles, briefings, discussion, applied research, case and comparative studies, expert comment and analysis on the key issues surrounding the Youth, Sports, and Health Education, and its various aspects. Analysis will be practical and rigorous in nature.Bandung, Indonesia: October 28, 2015.Andi SUWIRTAChairperson of ASPENSI; and a Senior Lecturer at the FPIPS UPI (Faculty of Social Studies Education, Indonesia University of Education) in Bandung, West Java, Indonesia.